Implementasi Pendidikan Karakter di SD Negeri 105 Palembang - Agustina, Weni; Lestari, Dinna (Journal of Innovation in Teaching and Instructional Media, 2024)
This study aims to examine the implementation of character education at SD Negeri 105 Palembang within the framework of the Merdeka Curriculum. Using a qualitative descriptive approach, data was gathered through observations, interviews with 10 teachers and 15 parents, and questionnaires distributed to 30 students. The findings reveal that character education, in line with the values of the Pancasila Student Profile, has been effectively incorporated, although there are challenges such as limited resources and a lack of parental involvement. Teachers utilize flexible teaching strategies, like project-based learning, to instill values such as collaboration, independence, and creativity. This study demonstrates how the flexibility of the Merdeka Curriculum enables a more adaptive and personalized approach to character education in elementary schools. The results also stress the importance of stronger collaboration between schools, parents, and the community to optimize students' character development. This research contributes to the discussion on character education in Indonesia, particularly within the context of the Merdeka Curriculum, which offers more opportunities for teachers to innovate and develop education that meets students' needs. The study provides insights into how character education can be implemented within the framework of the Merdeka Curriculum at SD Negeri 105 Palembang.